PELAKSANAAN PELAYANAN PUBLIK DI KECAMATAN PUCUK RANTAU KABUPATEN KUANTAN SININGI - Raja Sihornas; Zulkarnaini " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This research is motivated by the lack of maximum service provided of Pucuk Rantau sub-district office of Kuantan Singingi Regency to the societyand also high quality of claim public services to the sub-district office. Although this claimis often do not match with the expectations. Empirically, public services still characterized by a complicated, slowly, expensive and tiring. There are many kinds of public service business in the Pucuk Rantau sub-district office is often reaped protests such as less effective and efficient of these services.The purpose of this research is to know the implementation of public service Pucuk Rantau sub-district office in Kuantan Singingi regency, besides that to know the factors inhibiting the implementation of public service at the sub-district office of Pucuk Rantau in Kuantan Singingi Regency. In this research the writers was use descriptive qualitative research methods, this research method aims to analyze and illustrated how the implementation of society services in the sub-district office of Pucuk Rantau in Kuantan Singingi regency. In this study the subject is the official and the society were conduct service activities while the object of study is the implementation of Pucuk Rantau office in providing services to the society. In this research there is a plan of thought as a reference in developing problems to the researchers, the space of service is based on the principle of good service proposed by Sinambela.The result of the study is found that public service in Pucuk Rantau Head Office still needs to be improved, both in terms of Human Resource and in terms of completeness of facilities and infrastructure in implementing public services, so that what people expect in Pucuk Rantau District will be realized. One of the issues that need to be paid attention in the Office of Pucuk Rantau head is the professionalism of employees to be more disciplined in carrying out duty as a service provider to the public.Keywords: Implementation, Service, Public